A MODEL FOR FORMING BUSINESS RESILIENCE IN INDONESIA: A FAMILY BUSINESS PERSPECTIVE - Muhammad Nur Alam Muhajir; Andi Muh Almahdy; Alda; Syahrul Fitra (Journal of Management and Islamic Finance, 2024)
This research aims to identify a family business resilience model by considering anthropomorphism factors, innovation capabilities, and Islamic business ethics amidst slowing economic growth in Indonesia. The method used is quantitative using questionnaires and data analysis using Structural Equation Modeling Partial Least Square (SEM-PLS). Respondents consisted of 180 middle to upper family business owners in Indonesia. The research results show that anthropomorphism has a significant influence on family business resilience. However, these findings also show that the application of Islamic business ethics does not have a significant relationship in moderating the relationship between anthropomorphism and family business resilience. This research provides valuable insights into how the application of anthropomorphism and innovation capabilities can significantly increase the resilience of family businesses. The insignificance of Islamic business ethics on family business resilience indicates that the application of Islamic values in business practices has not been optimal. It suggests the need for better alignment with the context of modern business and the strengthening of the implementation of Sharia principles in company operations.